Restoring Public Trust: Analyzing Corruption Cases and Their Impact on Governance in Indonesia - Darmawan, Joko Budi; Suhariadi, Fendy; Widjojo, Suparto; Amiati, Mia (RSF Conference Series: Business, Management and Social Sciences, 2024)
Public trust in state administrators is being torn apart by corruption scandals. The public can see how corrupt behavior occurs sporadically at almost all levels of government. This article presents the results of research in the form of the phenomenon of criminal acts of corruption, which is closely related to the emergence of a level of public trust in Indonesia’s law and government. This study is a qualitative research using the literature review method. The approach used in this paper is a review and analysis of the case along with all relevant laws and regulations. The results of this research are that the criminal corruption case that ensnared Firli Bahuri included two types of crimes, namely, extortion, which involves the abuse of power to force civil servants or state administrators to provide personal benefits, as defined in Article 368 of the Criminal Code, which can lead to a prison sentence of up to nine years. The implication of this research is the need to strengthen supervision and consistent implementation of the law and restore the integrity of law enforcement institutions to prevent corruption and restore public trust.